Our Right to Share, Their Right to Know - Ezekiel, Kezia (University of Jember, 2021)
The defamation reports have increased and shifted under online-based technology through social media. This study considered the defamation issue in Indonesia that alleged Richard Lee, a doctor who shared a beneficial publication through social media about the dangerous skincare product. Richard's audience believed that his content helped them know the hidden truth behind skincare products available in the market. Consequently, the public questioned whether he was liable because he was regarded to share helpful information under the public interest. This study aimed to analyze Indonesia’s defamation laws, especially in public interest defense under Article 310(3) of the Indonesian Criminal Code. However, the interpretation for public interest as a crime abolition is unclear, resulting in various courts' decisions that lead to criminalizing internet users. This study used legal research with statutory and comparative approaches. It examined legal norms and practices in Indonesia and compared those in the United Kingdom, Canada, and New Zealand. These three countries adapted defamation law to develop cases, including those alleged defamations for the public interest. While the freedom of expression is enshrined in the constitution, its practice has contradicted defamation provisions outlined in derivative regulations. By comparison, these three countries have precise boundaries and public interest defense is explicit. Those countries have specific rules and lists that needed to be fulfilled for those who use public interest defense. The lists based on previous precedents show how they learn and adapt to the development of public interest defense in many cases. This study concluded that Indonesia does not have specific standards or rules to determine cases categorized as the public interest. KEYWORDS: Public Interest Defense, Online Defamation, Freedom of Expression.